The IVAIRE project – a randomized controlled study of the impact of ventilation on indoor air quality and the respiratory symptoms of asthmatic children in single family homes. (21st January 2015) - Lajoie, P.; Aubin, D.; Gingras, V.; Daigneault, P.; Ducharme, F.; Gauvin, D.; Fugler, D.; Leclerc, J.‐M.; Won, D.; Courteau, M.; Gingras, S.; Héroux, M.‐È.; et al.
Abstract: A randomized controlled trial was carried out to measure the impact of an intervention on ventilation, indoor air contaminants, and asthma symptoms of children. Eighty‐three asthmatic children living in low‐ventilated homes were followed over 2 years. Several environmental parameters were measured during the summer, fall, and winter. The children were randomized after Year 1 (43 Intervention; 40 Control). The intervention included the installation of either a Heat Recovery Ventilator (HRV) or Energy Recovery Ventilator (ERV). During the fall and winter seasons, there was a significant increase in the mean ventilation rate in the homes of the intervention group. A statistically significant reduction in mean formaldehyde, airborne mold spores, toluene, styrene, limonene, and α ‐pinene concentrations was observed in the intervention group. There was no significant group difference in change in the number of days with symptoms per 14 days. However, there was a significant decrease in the proportion of children who experienced any wheezing (≥1 episode) and those with ≥4 episodes in the 12‐month period in the intervention group. This study indicates that improved ventilation reduces air contaminants and may prevent wheezing. Due to lack of power, a bigger study is needed.